2022
DOI: 10.1111/1750-3841.16270
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed light of near‐infrared and visible light wavelengths induces the accumulation of carotenoids in tomato fruits during post‐treatment time

Abstract: Pulsed light (PL) is proposed as a novel strategy for the food industry to enhance the antioxidant potential of fruits and vegetables for industrial uses. The main aim of this work is to evaluate the impact of postharvest PL treatments of different spectral ranges on the carotenoid concentration as well as quality attributes of tomatoes during post‐treatment time. Doses of wide‐spectrum light (180–1100 nm), full‐spectrum without ultraviolet (UV)‐C wavelengths (305–1100 nm), and visible (VIS) + near‐infrared li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…However, other studies demonstrated that PL treatments could increase the contents of bioactive components in fruits and vegetables. For example, PL treatments promoted the total carotenoid accumulation in tomato fruits by modulating the phytoene synthase activity . Additionally, PL treatments enriched the phenolic compounds (by 55%) in melons by increasing PAL activity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies demonstrated that PL treatments could increase the contents of bioactive components in fruits and vegetables. For example, PL treatments promoted the total carotenoid accumulation in tomato fruits by modulating the phytoene synthase activity . Additionally, PL treatments enriched the phenolic compounds (by 55%) in melons by increasing PAL activity .…”
Section: Resultsmentioning
confidence: 99%
“…For example, PL treatments promoted the total carotenoid accumulation in tomato fruits by modulating the phytoene synthase activity. 30 Additionally, PL treatments enriched the phenolic compounds (by 55%) in melons by increasing PAL activity. 17 These differences can be attributed to the intensity of the PL treatment.…”
Section: Changes Of Total Anthocyanin Contents In Blood Oranges After...mentioning
confidence: 99%
“…Hence, studying the effect of light absorbance of bioactive compounds on the microbial inactivation efficiency by light pulses becomes important (Vollmer et al, 2020). Furthermore, it has been reported that the temperature gradient induced by the infrared portion of light in the PL treatment (Basak et al, 2022; González‐Casado et al, 2022), heats the surface layer of food, transferring the heat to the interior of the product. Despite stabilizing the temperature post‐PL treatment, photothermal damage occurs in the microbial cell membranes that combine with the PL photochemical mechanism and induces cell death of the microorganisms (Dunn et al, 1989; Wekhof, 2000; Wiktor et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Проведено изучение действия послеуборочной обработки PL различных спектральных диапазонов на содержание каротиноидов и качественные характеристики томатов при хранении после обработки [9]. Сравнивались широкий спектр (180-1 100 нм), полный спектр без ультрафиолетового УФ-С или без видимого (VIS) + ближнего инфракрасного (NIR) (400-1100 нм).…”
unclassified